Interactions between atrial fibrosis and inflammation in atrial fibrillation - Pang, Zhihua; Ren, Ying; Yao, Zhuhua (Frontiers in Cardiovascular Medicine, 2025)
Atrial fibrillation (AF) is a complex arrhythmia driven by intricate pathophysiological mechanisms, with atrial fibrosis and inflammation emerging as central players in its initiation and perpetuation. Key pathways, including the renin-angiotensin-aldosterone system (RAAS), TGF-β/Smad signaling, and pro-inflammatory cytokine cascades (e.g., TNF-α/NF-κB, IL-6/STAT3), contribute to fibrotic remodeling and electrophysiological dysfunction. These pathways promote extracellular matrix deposition, fibroblast activation, and heterogeneous conduction, creating a substrate for AF maintenance. Contemporary therapeutic approaches predominantly target rhythm control via catheter ablation techniques and pharmacological interventions with antiarrhythmic agents. Nevertheless, the efficacy of anti-inflammatory approaches, such as corticosteroids and colchicine, remains uncertain due to limited robust clinical evidence, highlighting the need for further investigation. Advanced fibrosis quantification modalities, particularly late gadolinium-enhanced magnetic resonance imaging and electroanatomic mapping, have emerged as valuable tools for optimizing ablation strategies. Furthermore, emerging evidence highlights significant sex-based disparities in atrial fibrosis distribution and electrophysiological substrate characteristics, suggesting the potential for gender-specific therapeutic approaches. This comprehensive review systematically examines the pathophysiological roles of atrial fibrosis and inflammation in AF progression, with particular emphasis on their intricate bidirectional relationship. Through detailed elucidation of these mechanistic interactions, we aim to facilitate the development of novel therapeutic interventions to enhance clinical management of AF.